Comparison of Intensity Analysis and the land use dynamic degrees to measure land changes outside versus inside the coastal zone of Longhai, China. (June 2018) - Huang, Boqiang; Huang, Jinliang; Gilmore Pontius, Robert; Tu, Zhenshun
Highlights: We compare in theory and practice two methods to indicate change among categories. Intensity Analysis shows graphically the sizes and intensities of various changes. We recommend that scientists not use the comprehensive land use dynamic degree. The single land use dynamic degree fails to show annual sizes of loss and gain. An example shows Intensity Analysis is more helpful than land use dynamic degrees. Abstract: We compare two popular methods to quantify temporal change among categories: 1) Intensity Analysis and 2) the land use dynamic degrees. We apply the methods to measure land change both outside and inside the coastal zone of Longhai, which is a typical county-level coastal city in Southeast China. The maps show eight categories at four time points: 1986, 1996, 2002, and 2010. Intensity Analysis shows graphically the size and the intensity of changes at three increasingly detailed hierarchical levels in a manner that facilitates interpretation. In contrast, the comprehensive land use dynamic degree (CLUDD) has no practical interpretation because the CLUDD is the sum of loss intensities of categories that have different sizes. The single land use dynamic degree is the annual net change as a percentage of the initial size of the category, which offers limited information because the single degree: 1) fails to reveal the sizes of the category's loss and gain, 2) does not indicate how each category contributes to total change, 3) is sensitive to the category's initial size, and 4) reveals neither the size of the category's annual net change nor the size of the category's initial size.